2015
DOI: 10.1002/admi.201500509
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterning of BiVO4 Thin Films Using Laser‐Induced Crystallization

Abstract: Relatively high temperatures even up to 500 °C are required to obtain bismuth vanadate (BiVO4) films with the scheelite monoclinic (s‐m) structure that shows the highest photocatalytic activity. This requirement limits the possible choice of substrates. Moreover, high quality thin layers of crystalline BiVO4 cannot be prepared with current methods. In this study a light‐induced crystallization approach is presented, which is a step toward preparation and patterning of BiVO4 (s‐m) films for applications on plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Although the simplicity of such processes offers important advantages, it tends to create relatively high defect densities (>10 18 cm À3 ) in the form of intrinsic point defects (e.g., cation and oxygen vacancies) as well as non-crystalline phases. 5 While some of these defects can promote the conductivity and therefore improve the PEC performance of the photoelectrode material, 6-9 many of these defects form electronic states deep in the bandgap of the oxide. Such states act as efficient charge carrier trapping or recombination centers, resulting in short carrier lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the simplicity of such processes offers important advantages, it tends to create relatively high defect densities (>10 18 cm À3 ) in the form of intrinsic point defects (e.g., cation and oxygen vacancies) as well as non-crystalline phases. 5 While some of these defects can promote the conductivity and therefore improve the PEC performance of the photoelectrode material, 6-9 many of these defects form electronic states deep in the bandgap of the oxide. Such states act as efficient charge carrier trapping or recombination centers, resulting in short carrier lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…Ground powder was pressed into a pellet and annealed at 500 °C for 4 h. Then, the material was ground again and pressed in a hydraulic press (Specac Ltd) for about 60 s, with a load of about 35 MPa, into a pellet that acted as a PLD target. The procedure was developed and published previously [32]. PLD was used to deposit BiVO 4 films on titania nanotubes (before annealing) or titanium foil.…”
Section: Methodsmentioning
confidence: 99%
“…The results are in good agreement with the XRD grain size result. [43,44] The increase in particle size may influence the surface roughness of the film. It is identified that BVO5 thin film has higher surface roughness than BVO3 thin film.…”
Section: Surface Morphology Analysismentioning
confidence: 99%